2002
DOI: 10.1080/02786820290092168
|View full text |Cite
|
Sign up to set email alerts
|

Thermophoresis in Rarefied Gas Flows

Abstract: Numerical calculations are presented for the thermophoretic force acting on a free-molecular, motionless, spherical particle suspended in a rare ed gas ow between parallel plates of unequal temperature. The rare ed gas ow is calculated with the direct simulation Monte Carlo (DSMC) method, which provides a timeaveraged approximation to the local molecular velocity distribution at discrete locations between the plates. A force Green's function is used to calculate the thermophoretic force directly from the DSMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 32 publications
4
33
0
2
Order By: Relevance
“…The thermophoretic effect on particle deposition has been a long time topic for experimental [2][3][4][5] and numerical [6][7][8] investigations. The thermophoretic effect on particle deposition has been a long time topic for experimental [2][3][4][5] and numerical [6][7][8] investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermophoretic effect on particle deposition has been a long time topic for experimental [2][3][4][5] and numerical [6][7][8] investigations. The thermophoretic effect on particle deposition has been a long time topic for experimental [2][3][4][5] and numerical [6][7][8] investigations.…”
Section: Introductionmentioning
confidence: 99%
“…On the numerical calculation side, Gallis et al [6][7][8] presented many articles for thermophoresis on rarefied gas flows. Gas heat flux and particle thermophoretic forces for Ar, He, and N 2 were given for 1 cm spacing between a cold plate and a warm plate over a pressure range from 0.1 mTorr to 1 Torr.…”
Section: Introductionmentioning
confidence: 99%
“…The movement of the particle resulted from this force is called thermophoresis. Thermophoresis is of practical interest in a wide range of applications including dust collectors (thermal precipitators) [1,2] and protection of critical surfaces from contaminant particles [3,4]. Over a century ago, Tyndall [5] observed that dust particles suspended in a gas with inhomogeneous temperature tend to move out of the hot regions.…”
Section: Introductionmentioning
confidence: 99%
“…The force on a particle was determined by applying the force Green's function to the molecular velocity distribution computed by DSMC (Gallis et al 2001). Care was taken to ensure that the numerical parameters yielded accurate results (Gallis et al 2001(Gallis et al , 2002a(Gallis et al , 2002b; in particular, the simulations were run for long times to minimize the statistical uncertainties inherent in molecular gas dynamics methods.…”
Section: Theorymentioning
confidence: 99%